Critical notes on the identity and distribution of Sonneratia griffithii Kurz (Lythraceae) in India – a critically endangered mangrove species. (7th February 2019) - Ragavan, P.; Dubey, Sourav Kumar; Panda, Muktipada; Deyroy, Malancha; Ravichandran, K.; Trivedi, Raman K.; Jayaraj, R. S. C.; Mohan, P. M.; Rana, T. S.
Abstract : The identity and distribution in India of Sonneratia griffithii Kurz, a critically endangered mangrove species, is validated and corrected. Field surveys showed that S. griffithii only occurs in the Andaman Islands and that specimens from the Indian Sundarbans and Odisha previously misidentified as S. griffithii instead belong to S. alba . An updated taxonomic description and illustration is provided, and the key distinguishing characters of the Sonneratia species found in the study are discussed with the aim to solve any uncertainty about the identity and nomenclature of Indian Sonneratia species.